INISIASI DESA MANDIRI BERBASIS URBAN FARMING UNTUK MEWUJUDKAN KETAHANAN PANGAN DI ERA PANDEMI COVID-19 - Rysca Indreswari; Mercy Bientri Yunindanova; Ana Agustina; Dwi Apriyanto; Edi Paryanto; Rizki Puspita Dewanti; Hardian Ningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract The Covid-19 pandemic that has emerged since the end of 2019 has threatened the issue of household food security. For this reason, food security must begin to be increased at the household level, both in rural and urban areas. Urban Farming is a concept of cultivating food crops carried out in urban areas. So far, urban farming has become a trend for food fulfillment in urban areas for plant and environmentalists due to technology that allows cultivation on limited land and with an aesthetic touch. With the Covid-19 pandemic, urban farming must be organized more seriously to achieve food security. For this reason, the authors with the Women Farmers Group (KWT) Ireng Manis from Temu Ireng hamlet, Tegal Gede village, Karanganyar regency will initiate an independent village based on urban farming to realize food security. The method used in this activity is Participatory Rural Appraisal (PRA). Participatory Rural Appraisal is an approach method in the process of empowering and increasing community participation, which emphasizes community involvement in the overall program of activities. There are four stages planned in this program, including: 1). socialization of urban farming concepts and provision of cultivation techniques for members of KWT Ireng Manis, 2). Arrangement of cultivation area with functional aesthetic concept, 3). Launching and promotion through social media, You Tube, print and online mass media, 4). Copyright registration and dissemination/publication of program results. The benefit of this program is the realization of an independent village based on urban farming to achieve food security. Abstrak Pandemi Covid-19 yang muncul sejak akhir tahun 2019 telah mengancam isu ketahanan pangan tingkat rumah tangga. Untuk itu, kemandirian pangan harus mulai ditingkatkan kembali di level rumah tangga baik di pedesaan maupun perkotaan. Urban Farming merupakan suatu konsep budidaya tanaman pangan yang dilakukan di perkotaan. Selama ini urban farming menjadi tren pemenuhan pangan di perkotaan untuk para pencinta tanaman dan lingkungan dikarenakan teknologi yang memungkinkan budidaya di lahan terbatas dan dengan sentuhan estetik. Dengan pandemic Covid-19, urban farming harus diorganisir dengan lebih serius untuk mewujudkan ketahanan pangan. Untuk itu tim pengusul bersama dengan Kelompok Wanita Tani (KWT) Ireng Manis Dukuh Temu Ireng, Kelurahan Tegal Gede, Kabupaten Karanganyar akan melakukan inisiasi desa mandiri berbasis Urban Farming untuk Mewujudkan ketahanan pangan. Metode yang digunakan dalam kegiatan ini adalah Participatory Rural Appraisal (PRA). Participatory Rural Appraisal merupakan suatu metode pendekatan dalam proses pemberdayaan dan peningkatan partisipasi masyarakat, yang tekanannya pada keterlibatan masyarakat dalam keseluruhan program kegiatan. Terdapat empat tahapan yang direncanakan dalam program ini, meliputi: 1). sosialisasi konsep urban farming dan pembekalan teknik budidaya bagi anggota KWT Ireng Manis, 2). Penataan areal budidaya dengan konsep estetik fungsional, 3). Launching dan promosi melalui sosial media, You Tube, media massa cetak dan online, 4). Pendaftaran hak cipta dan diseminasi/ publikasi hasil program. Manfaat dari program ini adalah terwujudnya desa mandiri berbasis urban farming untuk mewujudkan ketahanan pangan.